Antioxidant Properties of TeNan Herbal Tea Formulation “Telang (Clitoria ternatea) and Pineapple (Ananas comosus)” - Wahyu Widowati; Teresa Liliana Wargasetia; Meganita Marthania; Tazkia Salma Hanifa; Teddy Marcus Zakaria; Michael Sebastian Gunadi; Natanael Halim; Sheryl Santiadi (Fakultas Kedokteran Universitas Brawijaya, 2022)
Herbal teas was are widely consumed by people around the world have high antioxidant activities. The flavor and color combination of specific teas enriches the aroma and appearance of the tea, producing a tea with fresh color and tastier flavor. This study determines the antioxidant activity of telang flower tea (Clitoria ternatea), pineapple tea (Ananas comosus), and the formula of the combination of telang flower tea and pineapple tea called TeNan. The antioxidant activities of herbal teas were measured by 2,2 Diphenyl-1-picrylhydrazyl (DPPH), Hydrogen Peroxide (H2O2), 2,2′-Azino-bis(3-ethylbenzthiazoline-6-sulfonic acid) (ABTS), Ferric Reducing Antioxidant Power (FRAP) assay. The total phenol measurement used Gallic Acid Equivalent (GAE), while the flavonoid content measurement used Quercetin Equivalent (QE). The DPPH scavenging activities of telang flower tea, pineapple tea, and TeNan tea (IC50: 17.07%, 11.81%, and 22.22%), H2O2 scavenging activities (IC50: 26.62%, 41.81%, and 96.22%), ABTS-reducing activities (IC50: 2.51%, 3.39%, and 1.02%), and FRAP activities (IC50: 5.56%, 18.67%, and 7.48%). The total phenolic and flavonoid contents of TeNan tea were lower (9.44 μg GAE/100%; 3.46 μg QAE/100% sample concentration) than those of telang flower tea (16.20 μg GAE/100%; 4.88 μg QAE/100% sample concentration) but higher than those of pineapple tea (0.82 μg GAE/100%; 0.17 μg QAE/100% sample concentration). TeNan tea has the higher in ABTS and FRAP activities but lower in H2O2 and DPPH scavenging activities compared to telang flower tea and pineapple tea. In summary, telang tea has stronger antioxidant activity compared to pineapple and TeNan tea in FRAP and H2O2 assays.